1988
DOI: 10.1016/0033-5894(88)90084-1
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of Grain Size Distribution in Pleistocene Sediments from Lake Biwa, Japan

Abstract: Time series of grain-size distributions from Pleistocene sediments deposited in Lake Biwa during the past 550 millennia show dominant periods of 40,000 and 20,000 yr that are very close to those predicted by the Milankovitch theory, as well as a period of about 70,000 yr not directly predicted by this theory. The 70,000-yr period is strongest, followed by the 20,000-yr period. The sequences also show that coarser particles were deposited, in general, during strong solar insolation, whereas finer particles were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…A longer period of 60,000 yr is also indicated in Table 2 although its detection is not considered reliable in view of the short time interval (130,000 yr) covered by the data. However, a periodicity of 60,000 yr may exist, because 60,000-to 70,000-yr periodicities have been reported in other terrestrial data sets, as well as in deep-sea data sets (Kashiwaya et al, 1988(Kashiwaya et al, , 1990.…”
Section: Analysesmentioning
confidence: 95%
See 1 more Smart Citation
“…A longer period of 60,000 yr is also indicated in Table 2 although its detection is not considered reliable in view of the short time interval (130,000 yr) covered by the data. However, a periodicity of 60,000 yr may exist, because 60,000-to 70,000-yr periodicities have been reported in other terrestrial data sets, as well as in deep-sea data sets (Kashiwaya et al, 1988(Kashiwaya et al, , 1990.…”
Section: Analysesmentioning
confidence: 95%
“…Recently, several types of terrestrial records have been found to vary with Milankovitch frequencies (1941) during the past 150,000 to 250,000 yr, for example, Lake Biwa sediments in Japan (Yamamoto et al, 1984(Yamamoto et al, , 1985Kashiwaya et al, 1987Kashiwaya et al, , 1988 and the Vostok ice core in Antarctic (Barnola et al, 1987;Jouzel et al, 1987). Long-term climatic changes in Britain also have probably been controlled by global climatic changes.…”
Section: Introductionmentioning
confidence: 99%
“…The particle size distribution of the sediment is mainly controlled by factors such as the transport medium, the handling mode, and the deposition environment. Therefore, the sedimentary environment in which the sediment was deposited can be understood by studying the sediment particle size distribution [50][51][52][53]. The surface sediments of the ancient Milan River channel collected in this study are mainly composed of 6 types of sediment: fine slit, fine silt sand, medium silt sand, coarse silt sand, very coarse silt sand, and very fine sand.…”
Section: Sedimentary Environment Of the Ancient Milan River Channelmentioning
confidence: 99%